2011
DOI: 10.1037/a0024395
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of internalizing, externalizing, and academic adjustment among children of deployed military service members.

Abstract: Parental deployment during military conflicts has the potential to impact child adjustment. As increased numbers of military Service members have children, it is critical to understand the association between military deployment and child adjustment. In order to resolve inconsistencies in the existing literature, we performed a meta-analytic review of 16 studies that report associations of military deployment with internalizing, externalizing, and academic adjustment among children. Results indicate a small as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 52 publications
(75 reference statements)
7
107
1
Order By: Relevance
“…There may be increased behavior problems (Barker & Berry, 2009), problems at school (Pfefferbaum, Houston, Sherman, & Melson, 2011;Richardson et al, 2011), and increased family conflict (Knobloch et al, 2015). However, a meta-analysis of 16 studies of children of deployed service members showed small effect sizes and mixed results (Card et al, 2011). The authors of this meta-analysis caution that these results do not mean that children are unaffected by deployment.…”
Section: Review Of Literature Deploymentmentioning
confidence: 47%
See 1 more Smart Citation
“…There may be increased behavior problems (Barker & Berry, 2009), problems at school (Pfefferbaum, Houston, Sherman, & Melson, 2011;Richardson et al, 2011), and increased family conflict (Knobloch et al, 2015). However, a meta-analysis of 16 studies of children of deployed service members showed small effect sizes and mixed results (Card et al, 2011). The authors of this meta-analysis caution that these results do not mean that children are unaffected by deployment.…”
Section: Review Of Literature Deploymentmentioning
confidence: 47%
“…The effects may be different for reserve component families because they may have less access to resources and social support compared with active duty families located on or near military installations (Castenada et al, 2008;Lara-Cinisomo et al, 2013;Park, 2011). Other factors include individual and contextual factors such as personal characteristics, coping style, social support, parent and family functioning, and the availability of community supports (Card et al, 2011). The issues faced by military youth co-occur with normative developmental changes (Millburn & Lightfoot, 2013).…”
Section: Review Of Literature Deploymentmentioning
confidence: 99%
“…Internalizing or externalizing disorders may appear in these youth, as well as disruptions in family or peer relationships and academic maladjustment (Card et al, 2011;Chandra, L. Martin, et al, 2010). Many of these systemic responses by spouses and children can be traced to the experience of boundary ambiguity in this population (Faber et al, 2008;Huebner, Mancini, Wilcox, Grass, & Grass, 2007), as family members re-organize their perceptions of who is functionally in or out of the family system and in what particular ways.…”
Section: Post-deployment Military Family Functioningmentioning
confidence: 99%
“…While this may be protective during deployment, it can be destructive to family relationships if maintained once the service member is home. Also, during deployment, the at-home caregiver may enlist one of his or her children as a confidant (Card et al, 2011), which could have a temporary effect of strengthening that relationship. However, depending on the content, intensity, and duration of the confidant relationship, there could be detrimental consequences during reintegration should one or the other family members not want to give up that role.…”
Section: Boundary Ambiguity and Ambivalence 44mentioning
confidence: 99%
See 1 more Smart Citation